2006
DOI: 10.1158/0008-5472.can-05-4007
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Highly Active Nanoliposomal Irinotecan Using a Novel Intraliposomal Stabilization Strategy

Abstract: Liposome formulations of camptothecins have been actively pursued because of the potential for significant pharmacologic advantages from successful drug delivery of this important class of anticancer drugs. We describe nanoliposomal CPT-11, a novel nanoparticle/liposome construct containing CPT-11 (irinotecan) with unprecedented drug loading efficiency and in vivo drug retention. Using a modified gradient loading method featuring a sterically hindered amine with highly charged, multivalent anionic trapping age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
294
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 319 publications
(298 citation statements)
references
References 22 publications
3
294
1
Order By: Relevance
“…Nanoliposomal irinotecan (nal-IRI; Onivyde, irinotecan liposome injection, MM-398, PEP02, BAX2398) comprises irinotecan encapsulated in a nanoparticle drug delivery system in the form of the irinotecan sucrose octasulfate salt with an average particle size of 110 nm (10,11). Nal-IRI in combination with 5-fluorouracil/ leucovorin (5-FU/LV) is approved for use in the United States, European Union, and Taiwan Health Authorities for the treatment of patients with metastatic pancreatic cancer after disease progression following gemcitabine-based therapy (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Nanoliposomal irinotecan (nal-IRI; Onivyde, irinotecan liposome injection, MM-398, PEP02, BAX2398) comprises irinotecan encapsulated in a nanoparticle drug delivery system in the form of the irinotecan sucrose octasulfate salt with an average particle size of 110 nm (10,11). Nal-IRI in combination with 5-fluorouracil/ leucovorin (5-FU/LV) is approved for use in the United States, European Union, and Taiwan Health Authorities for the treatment of patients with metastatic pancreatic cancer after disease progression following gemcitabine-based therapy (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the normal brain has been found to have a low concentration which may be beneficial, assuming that liposomes accumulate in brain tumors via leakage from malformed tumor microvasculature, as demonstrated by Munson et al 51 We explored a gradient-based method owing to its simplicity and efficient loading. 52,53 Earlier gradient loading studies reported that liposomal uptake of drugs was driven by neutral external pH and low internal pH. We tested this and other pH profiles in an effort to optimize loading and, for the first time, describe enhancement of loading by reversing the gradient profile, so that external pH was low while internal pH was neutral (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…Additional therapeutic advances are expected from studies evaluating strategies for depletion stromal, inhibition pathways of cancer (i.e., Hedgehog, RAS-RAF-MAPK and PI3K-AKT), new chemotherapeutic drugs (i.e., MM-398 irinotecan encapsulated into liposomal-based nano particles) [65,66] , or the new era of immunotherapy. The identification of biomarkers continues to be clinically challenging but essential in order to tailor therapy to specific patients' subgroups in which the maximal antitumour effect from novel agents can be obtained.…”
Section: Current Knowledgementioning
confidence: 99%